PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN DENGAN MENGGUNAKAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING ( Studi Pada Perusahaan Perbankan Yang terdaftar di Bursa efek Indonesia) - Maful Taufiq; Ade Fatma Lubis; Sri Mulyani (Program Magister Akuntansi Unsyiah, 2014)
The purpose of this study was to find out whether or not Good Corporate Governance (GCG) had influence on the financial performance of the Banking Company Registered in the Indonesian Stock Exchange, whether or not Good Corporate Governance (GCG) had influence on the financial performance of the Banking Company Registered in the Indonesian Stock Exchange through profit management as intervening variable, whether or not Good Corporate Governance (GCG) had influence on the profit managementof the Banking Company Registered in the Indonesian Stock Exchange, and whether or notthe profit management had influence on the financial performance of the Banking Company Registered in the Indonesian Stock Exchange. The population of this study was 31 banking companies registered in the Indonesian Stock Exchange and 18 of them were selected to be the samples for this study through purposive sampling technique. To measure the discretionary accrual, the data for this study were 72 data resulted from the observation of the data from 2006 to 2010 (5 years). The hypothesis was tested through linear regression analysis. The result of this hypotesis testing showed that the application of Good Corporate Governance (GCG) directly had a significant influence on the financial performance. The application of Good Corporate Governance (GCG) with profit management as intervening variable did not have any significant influence on the company’s performance meaning that profit management is not a good variable in mediating the relationship between Good Corporate Governance (GCG) and financial performance and Good Corporate Governance (GCG) did not have any significant influence on profit management, and profit management had a negative and insignificant influence on the financial performance. Keywords: Good Corporate Governance, Profit Management, Financial Peformance